Follicle-stimulating hormone administration affects amino acid metabolism in mammalian oocytes. Issue 4 (16th July 2019) - Tetkova, Anna; Susor, Andrej; Kubelka, Michal; Nemcova, Lucie; Jansova, Denisa; Dvoran, Michal; Del Llano, Edgar; Holubcova, Zuzana; Kalous, Jaroslav
Abstract: Culture media used in assisted reproduction are commonly supplemented with gonadotropin hormones to support the nuclear and cytoplasmic maturation of in vitro matured oocytes. However, the effect of gonadotropins on protein synthesis in oocytes is yet to be fully understood. As published data have previously documented a positive in vitro effect of follicle-stimulating hormone (FSH) on cytoplasmic maturation, we exposed mouse denuded oocytes to FSH in order to evaluate the changes in global protein synthesis. We found that dose-dependent administration of FSH resulted in a decrease of methionine incorporation into de novo synthesized proteins in denuded mouse oocytes and oocytes cultured in cumulus-oocyte complexes. Similarly, FSH influenced methionine incorporation in additional mammalian species including human. Furthermore, we showed the expression of FSH-receptor protein in oocytes. We found that major translational regulators were not affected by FSH treatment; however, the amino acid uptake became impaired. We propose that the effect of FSH treatment on amino acid uptake is influenced by FSH receptor with the effect on oocyte metabolism and physiology. Abstract : Summary Sentence FSH treatment decrease methionine incorporation into de novo synthesized proteins in mouse, porcine, and bovine oocytes, and FSHR protein is expressed in oocytes and 2cell embryo.